Polityka zagraniczna pierwszego rządu Partii Pracy w Wielkiej Brytanii w 1924 r. - Harasimowicz, Andrzej (Acta Universitatis Lodziensis. Folia Historica, 1981)
This book is a shortened version of the doctoral thesis completed in Historical Institute of the Łódź University, in 1977. In original version, there was a large chapter concerning Anglo-Soviet relations, omitted here because of the prior publication аs an article in ZNUŁ 1978, no 27. The thesis is based on British government archival materials, chiefly political correspondence, being kept in Public Record Office at London. These are Foreign Office – and Colonial Office paреrs. Another set of documents is from Labour Party's Central Archive at London (so called Transport House). These are mainly memoranda’s of the International Advisory Committee, 1918-1924.